82.8k views
4 votes
Name the postulate or theorem you can use to prove ADE=EBA?

Name the postulate or theorem you can use to prove ADE=EBA?-example-1
User Voivoid
by
5.9k points

1 Answer

4 votes

Answer:

(c) Δ ADE ≅ Δ EBA by AAS Theorem

Explanation:

Here, in Δ ACE

AC = CE (given)

Also, ANGLES OPPOSITE TO EQUAL SIDES ARE EQUAL.

⇒ ∠E = ∠A ..... (1)

Now, in Δ ADE and Δ EBA

∠E = ∠A (from above)

∠ADE = ∠ABC ( right angle)

AE = AE (common side)

hence, Δ ADE ≅ Δ EBA by AAS Theorem

As, by AAS Theorem (ANGLE ANGLE SIDE)

Two triangle said said to be congruent if 2 angles and 1 side of one triangle is equal to 2 corresponding angles and 1 corresponding side of the other triangle.

Hence, Δ ADE ≅ Δ EBA by AAS Theorem

User Bizzarrus
by
6.0k points